2020
DOI: 10.3389/fgene.2020.00136
|View full text |Cite
|
Sign up to set email alerts
|

SUNny Ways: The Role of the SUN-Domain Protein Mps3 Bridging Yeast Nuclear Organization and Lipid Homeostasis

Abstract: Mps3 is a SUN (Sad1-UNC-84) domain-containing protein that is located in the inner nuclear membrane (INM). Genetic screens with multiple Mps3 mutants have suggested that distinct regions of Mps3 function in relative isolation and underscore the broad involvement of Mps3 in multiple pathways including mitotic spindle formation, telomere maintenance, and lipid metabolism. These pathways have largely been characterized in isolation, without a holistic consideration for how key regulatory events within one pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 94 publications
(121 reference statements)
0
5
0
Order By: Relevance
“…The characterisation of the mps3-AAA and mps3-S189A and -S190A mutants revealed that Mps3 localisation to NE (NE remodelling) plays a unique role in NE expansion in meiotic cells. NE-bound Mps3 may regulate NE growth by directly promoting lipid synthesis on NE or by importing lipids from the ER ( Sosa Ponce et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The characterisation of the mps3-AAA and mps3-S189A and -S190A mutants revealed that Mps3 localisation to NE (NE remodelling) plays a unique role in NE expansion in meiotic cells. NE-bound Mps3 may regulate NE growth by directly promoting lipid synthesis on NE or by importing lipids from the ER ( Sosa Ponce et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…SUN1/2 are expressed in skeletal and cardiac muscles in humans ( Crisp et al, 2006 ; Puckelwartz et al, 2009 ; Zhang et al, 2010 ). They both have a C-terminal SUN domain, a coiled-coil domain, a transmembrane (TM) domain, and an N-terminus nucleoplasmic domain ( Stroud, 2018 ; Sosa Ponce et al, 2020 ). The SUN domain is the most conserved domain that interacts with the KASH domain on Nesprin ( Sosa et al, 2012 ; Wang et al, 2012 ; Sosa Ponce et al, 2020 ).…”
Section: Functions Of Nuclear Envelope and Nucleoskeleton Proteins In...mentioning
confidence: 99%
“…They both have a C-terminal SUN domain, a coiled-coil domain, a transmembrane (TM) domain, and an N-terminus nucleoplasmic domain ( Stroud, 2018 ; Sosa Ponce et al, 2020 ). The SUN domain is the most conserved domain that interacts with the KASH domain on Nesprin ( Sosa et al, 2012 ; Wang et al, 2012 ; Sosa Ponce et al, 2020 ). Inter-protein interactions between the coiled-coil domains form the SUN protein trimer ( Sosa et al, 2012 ; Jahed et al, 2018a ; Jahed et al, 2018b ; Sosa Ponce et al, 2020 ).…”
Section: Functions Of Nuclear Envelope and Nucleoskeleton Proteins In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the LINC and the SPB spatially co-localize in mitotic cells, whereas the LINC only spreads over the NE in meiosis, where it forms a specialized complex that connects telomeres to the cytoskeleton [ 38 ]. Mutants for both the LINC and SPBs share phenotypes of misshapen nuclei [ 39 ]. In addition, NPC mutants also lead to impressive aberrant NE morphologies as well [ 40 ].…”
Section: The Yeast Nucleus: a Model To Address Nuclear Morphology And...mentioning
confidence: 99%